Production, Purification and Characterization of Uricase Produced by Pseudomonas aeruginosa - K. Abdullah, Suhad; T.Flayyih, May (Iraqi Journal of Science, 2023)
In this study, detection of uricase production from Pseudomonas aeruginosaisolates was done by applying colorimetric method, Uricase was purified from themost potent isolate by precipitation using ammonium sulphate (80% saturation) thenpurification was achieved using DEAE –Cellulose ion exchange and Sepharose 6Bgel filtration chromatography column, 16.4% of total enzyme was recovered withspecific activity 2337.5U/mg and 22.21folds of purification. Characterization ofuricase involved detection of optimal conditions for uricase activity, the maximalactivity was obtained at temperature 45ºC,while uricase appeared to be stable at40ºC. Uricase showed optimal activity at pH 9 while pH stability was in therange of 7.5-9. Molecular weight of uricase obtained in this study determined bysodium dedosyl sulfate electrophoresis (SDS-PAGE) technique was approximately35kDa.